Efficacy of Single-Pill Combination of Telmisartan 80 mg and Hydrochlorothiazide 25 mg in Patients with Cardiovascular Disease Risk Factors: A Prospective Subgroup Analysis of a Randomized, Double-Blind, and Controlled Trial - Harold Bays; Pingjin Gao; Birgit Völker; Michaela Mattheus; Luis M. Ruilope; Dingliang Zhu (International Journal of Hypertension)
Objective. Report of prespecified and post hoc subgroup analyses of a randomized, controlled trial comparing telmisartan 80 mg/hydrochlorothiazide 25 mg (T80/H25) combination therapy with T80 monotherapy, according to the presence of cardiovascular disease (CVD) risk factors. Methods. Hypertensive patients were randomized (2 : 1) to receive T80/H25 or T80 for 6 weeks, following a 1-week, low-dose, and run-in period. Systolic blood pressure (SBP) and diastolic BP reductions and BP goal achievement were evaluated in patients with CVD risk factors: presence of diabetes mellitus (DM), renal impairment, increased body mass index (BMI), and 10-year estimated risk for coronary heart disease (CHD). Results. In total, 888 patients received treatment. Overall, T80/H25 therapy significantly reduced SBP more than T80 monotherapy, irrespective of patient subgroup. In patients with DM, renal impairment, high BMI, and high CHD risk, BP goal achievement rates (<140/90 mm Hg) at Week 7, among those treated with T80/H25, were 52.8%, 52.8%, 50.6%, and 38.5%, respectively. More patients with DM reached a guideline-based BP goal (<130/80 mm Hg) at 7 weeks with T80/H25 than with T80 monotherapy (16.7% versus 8.8%). Rates of treatment-related adverse events were low and comparable across patient subgroups. Conclusions. Antihypertensive treatment with T80/H25 single-pill combination is effective and generally well tolerated, irrespective of the presence of CVD risk factors.